Synthesis of bioactive Schiff base thiosemicarbazone analogs with quinoline for high-performance copper corrosion inhibition: Insights from RSM-assisted EIS, XPS, DFT, and MD studies - Muhammad Ammar, Mohamad Alwi; Mohammad Norazmi, Ahmad; Mohd Bijarimi, Mat Piah; Hariy, Pauzi; Erna, Normaya (Elsevier Ltd, 2025)
Developing novel corrosion inhibitors is essential for protecting metal surfaces in aggressive industrial environments. In this study, a thiosemicarbazone scaffold was synthesized and functionalized with a bioactive quinoline moiety to form 3-acetylquinoline thiosemicarbazone (QT), a potential copper corrosion inhibitor. Structural characterization of QT was conducted using FT-IR, ¹H and ¹³C NMR spectroscopy. The inhibition performance of QT was evaluated using gravimetric weight loss measurements and electrochemical impedance spectroscopy (EIS), with optimization achieved through Response Surface Methodology (RSM). Statistical analysis identified the optimum conditions—46.42 °C, 2.92 M HCl, 0.65 mM QT, and 23.22 hours—yielding an inhibition efficiency exceeding 97 %. Langmuir isotherm modeling confirmed monolayer chemisorption, while XPS and SEM analyses demonstrated strong QT–copper interactions via Cu–N and Cu–S coordination, with binding energies of 398.11 eV and 161.79 eV, respectively. Density Functional Theory (DFT) and molecular electrostatic potential (MEP) analysis indicated that the imine and thione groups serve as key adsorption sites. Global reactivity descriptors revealed low hardness (0.8473 eV) and high chemical softness (1.1802 eV⁻¹), consistent with high reactivity. Molecular dynamics (MD) simulations further confirmed a stable QT–Cu interaction with an adsorption energy of −764.546 kJ/mol. This integrated experimental–theoretical approach demonstrates QT’s strong potential as a high-performance, cost-effective corrosion inhibitor for use in acidic environments.